Odškodninska odgovornost za nasvet in informacije ter vprašanje zahtevkov tretjih oseb - Možina, Damjan (Podjetje in delo, 2015)
A provider of an advice, information or opinion is generally not liable for the loss caused by incorrect information (advice, information). However, liability can be established if the provider is an expert who enjoys special confidence and could have foreseen that the receiver will rely on the information. In certain cases the law provides for a liability of the expert not only against contract party, but also against a third party who relies on the information received. This is the case e.g. with regard to the liability of auditors. The author takes the view that experts are liable against third persons for loss caused by incorrect information also outside specific provisions of law. Such liability, however, needs to be limited: an expert is liable only against persons from an identifiable group of persons, if the expert could reasonably have foreseen that they will rely on the information in making a decision of certain kind. In developing such a liability, art. VI. 2:207 DCFR provides a useful guidance.
Keywords: informacije; odgovornost; odškodninska odgovornost; poslovno svetovanje; svetovanje